Employability of technology and livelihood education graduates - Reynald M. Cacho; Rodrigo D. Abenes; Ryan R. Dejapa; Hannah Rose D. Mapula (International Journal of Evaluation and Research in Education (IJERE), 2022)
This paper examines the job-seeking experiences of the 2019 Bachelor of Technology and Livelihood Education (BTLE) graduates from a teacher education university. Identifying these graduates’ employability is vital to the field of educational research, particularly in determining the impact of a higher education institution’s BTLE program. Employing quantitative research design through a survey of 50 graduates, this research revealed that great majority of them have been employed, with majority securing education-related jobs within a year after graduation, while some having chosen careers unrelated to their pre-service education. Strategies for job search and reasons for job offer acceptance vary from traditional, economic concerns, to complexities of work opportunities and requirements. They have also reported that the pre-service courseworks they undertaken have, to a great extent, relevance to the improvement of their skills in problem-solving, communication, critical thinking, human relations, knowledge/technical, leadership, research, and information technology thus making it aligned with current employment and/or self-employment demands. Apart from presenting the reasons of their employment acceptance and post-college education undertakings, this paper also outlines the challenges in securing employment. Thus, such issues forwarded by the paper, arising from academic training vis-à-vis actual industry works, are strong points for pre-service BTLE program enhancements.